Penerapan Sanksi Adat Kasepekang di Desa Adat Tanjung Benoa Kecamatan Kuta Selatan Kabupaten Badung - I Gede Yoga Paramartha Duarsa; I Nyoman Gede Sugiartha; Diah Gayatri Sudibya (Jurnal Konstruksi Hukum, 2020)
The customs and habits of the Hindu community in Bali are basically fostered, maintained, and led by an institution called Desa Adat, which is a village with a different position and function from the official village (government administrative village). There are regulations in the Balinese Traditional Village that must not be violated. If a violation is found, it will be given one of the sanctions, namely Kasepekang. Kasepekang is a Balinese customary sanction, where the recipient of the sanction will be excommunicated, exiled or terminated from activities in the village (Madesa). This is because the perpetrator has repeatedly violated the rules of the traditional village (outrageous), so that this sanction is deemed appropriate. If a person or group of village members is deemed to have violated legal norms, it is called â€œawig-awigâ€ in the Balinese traditional language. This study aims to determine the application of customary sanctions as well as obstacles in the application of customary sanctions in the Tanjung Benoa Traditional Village, South Kuta District, Badung Regency. This research method uses an empirical method that is guided by data collection techniques by direct interviews with those who are competent using the receptio theory, the theory of receptio in complexu in the concept of a rule of law to examine the current phenomenon in the orderliness of the life of the Tanjung Benoa Traditional Village community which is based on regulations. Bali Region Number 4 of 2019 concerning Traditional Village. The results showed that the implementation of the Kasepekang customary sanctions in the Tanjung Benoa Traditional Village was carried out by the traditional leaders, namely Kelihan Banjar or Kelihan Adat with several stages in the form of giving advice (pitutur ayu), giving a warning (penglemek) to being excluded (Kasepekang) from the activities of community social organizations. banjar. It is hoped that people will become aware of and follow what the Banjar Adat community has agreed to do.